2022
DOI: 10.3390/math10020260
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Deep Learning-Based State-of-Charge Estimation for Renewable Energy Management System in Hybrid Electric Vehicles

Abstract: In recent years, alternative engine technologies are necessary to resolve the problems related to conventional vehicles. Electric vehicles (EVs) and hybrid electric vehicles (HEVs) are effective solutions to decarbonize the transportation sector. It also becomes important to shift from traditional houses to smart houses and from classical vehicles to EVs or HEVs. It is needed to combine renewable energy sources (RESs) such as solar photovoltaics, wind energy systems, and various forms of bio-energies. Among va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 23 publications
(27 reference statements)
0
11
0
Order By: Relevance
“…In order to further assure the enhanced performance of the HBFOA-SAE model, a comparative examination with the deep learning based SOC (DLSOC) and optimal extreme learning machine (ELM) models takes place under distinct measures as shown in Tab. 4 [20,21]. After examining the results and discussion, it is confirmed that the HBFOA-SAE model has shown effective SOC estimation outcomes.…”
Section: Performance Validationmentioning
confidence: 79%
“…In order to further assure the enhanced performance of the HBFOA-SAE model, a comparative examination with the deep learning based SOC (DLSOC) and optimal extreme learning machine (ELM) models takes place under distinct measures as shown in Tab. 4 [20,21]. After examining the results and discussion, it is confirmed that the HBFOA-SAE model has shown effective SOC estimation outcomes.…”
Section: Performance Validationmentioning
confidence: 79%
“…Some current methods, designed to handle complex battery behaviors, may introduce overcomplication when applied to simpler battery systems. For EVs with straightforward battery designs, the added complexity may not necessarily translate into proportional benefits, leading to inefficiencies in terms of computational resources and implementation costs [70][71][72]. In simple battery systems, the added complexity resulted in an 11.17% increase in computational resources without significant improvement in accuracy, highlighting the inefficiency of applying complex models [51,54].…”
Section: ) Overcomplication For Simple Battery Systemsmentioning
confidence: 99%
“…The capacity degradation over time due to chemical processes and charge-discharge cycles poses a considerable challenge for precise SOC estimation [71][72][73].…”
Section: ) Challenges In Addressing Aging Effectsmentioning
confidence: 99%
“…Ref. [160] presents an intelligent estimation technique based-deep learning to estimate the SOC of BESS in conjunction with VRE coordination with hybrid EVs. The estimation of BESS is essential for microgrids, and an OMT can provide several approaches to optimise the BESS charging and discharging process.…”
Section: Optimal Management Techniquementioning
confidence: 99%